A Structural Damage Identification Method Based on Arrangement of the Static Force Residual Vector - Shen, Jibao; Li, Zhike; Luo, Shuai; Wang, Wei (Frontiers in Materials, 2022)
In order to effectively and conveniently identify the damage location and damage degree of structural members under static response, a structural damage identification method based on the force residual vector is proposed. The force residual vector is defined by using the static displacement data and the stiffness matrix of the finite element model structure. The structural element corresponding to the non-zero element of the permutation force residual vector is intelligently determined as the damage element. The damage degree of the damaged unit is calculated from the equilibrium equation, which is established by the global stiffness matrix with only the damaged unit. For example, the identification analysis of damage units of numerical models is carried out for a simply supported beam as a simple structure and a truss as a complex structure based on the proposed method. In El Centro seismic wave, the dynamic responses of the original model and truss damage model are simulated and compared by using state space theory to verify the necessity of damage identification.